Una carta en torno al escudo de armas de Mateo Vázquez de Leca en la "Corsica" de Calvete de Estrella - Díaz Gito, Manuel Antonio (2009)
Edition and commentary of a letter from the historian and poet Juan Cristóbal Calvete de Estrella to Philip II´s secretary, Mateo Vázquez de Leca. Calvete´s letter deals with a fragment of his poem Corsica in which the coat of arms of the Corsican family Lecca is accurately described; this is the first part of a study where the conection of this letter to the obscure lineage of Mateo Vázquez is analysed.
Edición y comentario de una carta del historiador y poeta Juan Cristóbal Calvete de Estrella al secretario privado de Felipe II, Mateo Vázquez de Leca, en la que se cuestiona un pasaje de su poema Corsica donde se describe con detalle el escudo de armas de la familia corsa Lecca; primera parte de un trabajo donde se aborda la relación de esta carta con el problema del oscuro origen familiar de Mateo Vázquez
Keywords: Calvete de Estrella, Juan Cristóbal, -- m. 1593; Vázquez de Leca, Mateo, -- 1542-1591; Cartas